A new species of Ocyale (Araneae, Lycosidae) from Madagascar, with first observations on the biology of a representative in the genus - Jocque, Merlijn; Wellens, Siel; Andrianarivosoa, J.D.; Rakotondraparany, F.; The Seing, Sam; Jocqué, Rudy (European Journal of Taxonomy, 2017)
A large white species of wolf spider, Ocyale ghost Jocque M. & Jocqué R. sp. nov., is described from a white sandy beach of an inland freshwater lake in the northwest of Madagascar. The first photos of a living specimen of the genus Ocyale are provided together with some observations on the biology of the newly described species. An updated and illustrated key to the Afrotropical species of Ocyale is included here.